Paper-based disposable electrowetting chip for microfluidic application - Ismail, Noor Faezah (2018)
In biology and chemical industries, there are lots of works to do in a laboratory with micron and nano-sized of samples, therefore these industries need low- cost disposable chips to able to repeat the testing frequently without consuming high cost. One example of a low cost chip is an electrowetting chip which using the electrowetting technique where it is one of the microfluidic system techniques. It is used to manipulate the microdroplet such as transportation, mixing, separation and microdroplet generation.